Failure of Colorectal Anastomosis: Risk Factors, Prevention, Diagnosis, Therapeutic Tactics - M. F. Cherkasov; A. V. Dmitriev; V. S. Groshilin; S. V. Pereskokov; M. A. Kozyrevskiy; A. A. Urupina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To analyse and generalize available literature data on the problem of colorectal anastomotic leakage after rectal resection. Key findings. Over the last decade, there has been an increasing trend towards sphincter-preserving operations in modern colorectal surgery. The widespread use of suturing devices of various diameters allows the formation of ultra-low anastomoses (at the level of the pelvic floor). One of the menacing complications after rectal resection is anastomotic leakage, which frequency can reach 21%. The mortality from anastomotic leakage can reach 40%. The analysed literature sources discuss a variety of risk factors, both preoperative and intraoperative, affecting the healing of the inter-intestinal anastomosis. In almost all studies, the height of the tumour and the anastomosis from the anus, preoperative radiotherapy and male sex are independent risk factors for the development of colorectal anastomotic leakage. Concerning other factors, there are conflicting opinions. The timely use of preventive measures and early diagnosis of colorectal anastomotic leakage can reduce the number and severity of postoperative complications.Conclusion. Individual consideration of risk factors and their adequate assessment in terms of possible complications are decisive in the choice of the extent of surgical intervention, which will undoubtedly improve the immediate and long-term results of the surgical treatment of colorectal cancer.